Implementation of Digital Archive Management in The Administration of International Missions Police Bureau - Rama Dian Syah; Antonius Angga Kurniawan; Mutiara Romana Kusuma; Rizki Ariyani (ISB Atma Luhur, 2026)
Advances in information technology have accelerated digital transformation in public sector administration, including archival management systems. However, limited studies have examined the implementation of digital archive systems within high-mobility and security-sensitive governmental units. This study aims to design and implement a digital archive management system for the administrative division of the International Missions Police Bureau (POLRI) to enhance correspondence supervision and operational efficiency. The research adopts the Waterfall development model, consisting of requirements analysis, system design, implementation, and testing stages. System requirements were identified through structured observation, semi-structured interviews, and literature review. The system was designed using use case modeling, database schema design, and flowchart analysis, and implemented as a web-based application using PHP and the CodeIgniter framework with a MySQL database. Functional validation was conducted using black box testing to ensure conformity between system features and specified requirements. The developed system includes modules for managing incoming letters, outgoing letters, official memoranda, archival records, and meeting room scheduling. Testing results indicate that all functional components operate according to expected specifications, demonstrating functional reliability and operational feasibility. The implementation of this system improves document traceability, administrative monitoring, and information accessibility without spatial and temporal limitations. This study contributes to the field of digital governance and information systems by providing an empirical implementation framework for digital archive management in a specialized law enforcement administrative context. The findings demonstrate the practical applicability of structured system development methods in supporting digital transformation within government institutions.